Safety and Efficacy of the Addition of Lapatinib to Perioperative Chemotherapy for Resectable HER2-Positive Gastroesophageal Adenocarcinoma: A Randomized Phase 2 Clinical Trial - Smyth, Elizabeth C. (JAMA Oncol, 2019)
IMPORTANCE: Perioperative chemotherapy and surgery are a standard of care for operable gastroesophageal adenocarcinoma. Anti-HER2 therapy improves survival in patients with advanced HER2-positive disease. The safety and feasibility of adding lapatinib to perioperative chemotherapy should be assessed. OBJECTIVES: To assess the safety of adding lapatinib to epirubicin, cisplatin, and capecitabine (ECX) chemotherapy and to establish a recommended dose regimen for a phase 3 trial. DESIGN, SETTING, AND PARTICIPANTS: Phase 2 randomized, open-label trial comparing standard ECX (sECX: 3 preoperative and 3 postoperative cycles of ECX with modified ECX plus lapatinib (mECX+L). This multicenter national trial was conducted in 29 centers in the United Kingdom in patients with histologically proven, HER2-positive, operable gastroesophageal adenocarcinoma. Registration for ERBB/HER2 testing took place from February 25, 2013, to April 19, 2016, and randomization took place between May 24, 2013, and April 21, 2016. Data were analyzed May 10, 2017, to May 25, 2017. INTERVENTIONS: Patients were randomized 1:1 open-label to sECX (3 preoperative and 3 postoperative cycles of 50 mg/m(2) of intravenous epirubicin on day 1, 60 mg/m(2) intravenous cisplatin on day 1, 1250 mg/m(2 )of oral capecitabine on days 1 through 21) or mECX+L (ECX plus lapatinib days 1 through 21 in each cycle and as 6 maintenance doses). The first 10 patients in the mECX+L arm were treated with 1000 mg/m(2) of capecitabine and 1250 mg of lapatinib per day, after which preoperative toxic effects were reviewed according to predefined criteria to determine doses for subsequent patients. MAIN OUTCOMES AND MEASURES: Proportion of patients experiencing grade 3 or 4 diarrhea with mECX+L. A rate of 20% or less was considered acceptable. No formal comparison between arms was planned. RESULTS: Between February 2013, and April 2016, 441 patients underwent central HER2 testing and 63 (14%) were classified as HER2 positive. Forty-six patients were randomized; 44 (24 sECX, 20 mECX+L) are included in this analysis. Two of the first 10 patients in the mECX+L arm reported preoperative grade 3 diarrhea; thus, no dose increase was made. The primary endpoint of preoperative grade 3 or 4 diarrhea rates were 0 of 24 in the sECX arm (0%) and 4 of 20 in the mECX+L arm (21%). One of 24 in the sECX arm and 3 of 20 in the mECX+L arm stopped preoperative treatment early, and for 4 of 19 in the mECX+L arm, lapatinib dose was reduced. Postoperative complication rates were similar in each arm. CONCLUSIONS AND RELEVANCE: Administration of 1250 mg of lapatinib per day in combination with ECX chemotherapy was feasible with some increase in toxic effects, which did not compromise operative management. TRIAL REGISTRATION: ISRCTN.org identifier: 46020948; clinicaltrialsregister.eu identifier: 2006-000811-12